Sustained effects on immune cell subsets and autoreactivity in multiple sclerosis patients treated with oral cladribine - Holm Hansen, Rikke; von Essen, Marina Rode; Reith Mahler, Mie; Cobanovic, Stefan; Sellebjerg, Finn (Frontiers in Immunology, 2024)
Cladribine tablet therapy is an efficacious treatment for multiple sclerosis (MS). Recently, we showed that one year after the initiation of cladribine treatment, T and B cell crosstalk was impaired, reducing potentially pathogenic effector functions along with a specific reduction of autoreactivity to RAS guanyl releasing protein 2 (RASGRP2). In the present study we conducted a longitudinal analysis of the effect of cladribine treatment in patients with RRMS, focusing on the extent to which the effects observed on T and B cell subsets and autoreactivity after one year of treatment are maintained, modulated, or amplified during the second year of treatment.In this case-control exploratory study, frequencies and absolute counts of peripheral T and B cell subsets and B cell cytokine production from untreated patients with relapsing-remitting MS (RRMS) and patients treated with cladribine for 52 (W52), 60 (W60), 72 (W72) and 96 (W96) weeks, were measured using flow cytometry. Autoreactivity was assessed using a FluoroSpot assay.We found a substantial reduction in circulating memory B cells and proinflammatory B cell responses. Furthermore, we observed reduced T cell responses to autoantigens possibly presented by B cells (RASGRP2 and α-B crystallin (CRYAB)) at W52 and W96 and a further reduction in responses to the myelin antigens Mmyelin basic protein (MBP) and Mmyelin oligodendrocyte glycoprotein (MOG) after 96 weeks.We conclude that the effects of cladribine observed after year one are maintained and, for some effects, even increased two years after the initiation of a full course of treatment with cladribine tablets.